Synthesis and physical properties of esters of 2-[5-((theophylline-7’-yl)methyl)-4-R-1,2,4-triazole-3-ylthio]acetic acid - Gotsulya, A. S.; Гоцуля, Андрій Сергійович; Гоцуля, А. С. (Zaporozhye state medical university, 2017)
The large synthetic potential and high biological potential in the series of 1,2,4-triazole derivatives cause favorable conditions for the search for new biologically active substances. A special attention is paid to the possibility of introducing various substituents at the stage of 1,2,4-triazole-3-thiol structure formation. At the same time, derivatives of xanthine are known as the basis for obtaining a wide range of drugs. The aim of this work was the synthesis and properties’ study of new compounds in the series of esters of 2-[5-((theophylline-7'-yl) methyl)-4-R-1,2,4-triazole-3-ylthio]acetic acids. Materials and methods. The strategy of the synthesis of all target products of the reaction was based on the use of theophylline as starting material. To obtain the intermediate thiol we used reactions of esterification, nucleophilic substitution, hydrazinolysis and intermolecular alkaline heterocyclic. The esters of 2-[5-((theophylline-7’-yl)methyl)-4-R-1,2,4-triazole-3-ylthio]acetic acid were obtained by two methods. The melting point was determined using capillary method on OptiMelt MPA 100 (SRS, USA). The structure of the compounds was confirmed with elemental analysis on Elemental Vario EL cube (Elementar Analysensysteme, Germany), IR spectra (4000–400 cm-1) were taken off the module ALPHA-T of Bruker ALPHA FT-IR spectrometer (Bruker optics, Germany). Chromate-mass-spectral studies were carried out on Agilent 1260 Series LC/MSD System. Conclusion. The optimal conditions of obtaining esters of 2-[5-((theophylline-7’-yl)methyl)-4-R-1,2,4-triazole-3-ylthio]acetic acid have been determined. 15 not described previously compounds have been synthesized, its structure has been confirmed by physical and chemical methods of analysis. It has been established that the synthesis of esters of 2-[5-((theophylline-7’-yl)methyl)-4-R-1,2,4- triazole-3-ylthio]acetic acid proceeds with greater yield, if they are gotten directly from the thiol. Великі синтетичні можливості та високий біологічний потенціал у ряду похідних 1,2,4-тріазолу зумовлюють сприятливі умови пошуку нових біологічно активних речовин. Особливу привабливість також викликає можливість уведення різних замісників на етапі формування структури 1,2,4-тріазол-3-тіолу. Водночас похідні ксантину відомі як основа для отримання широкого спектра лікарських засобів. Мета роботи – синтез і вивчення властивостей сполук у ряду складних ефірів 2-[5-((теофілін-7’-іл)метил)-4-R-1,2,4-тріазол- 3-ілтіо]ацетатної кислоти. Матеріали та методи. Стратегія синтезу всіх цільових продуктів реакції базувалась на використанні теофіліну як вихідної речовини. Для отримання проміжного тіолу використані реакції етерифікації, нуклеофільного заміщення, гідразинолізу та внутрішньомолекулярної лужної гетероциклізації. Ефіри 2-[5-((теофілін-7’-іл)метил)-4-R-1,2,4-тріазол-3-ілтіо]ацетатної кис¬лоти одержані за двома методами. Будова речовин підтверджена за допомогою елементного аналізу на приладі Elementar Vario ЕL cube (CHNS), ІЧ-спектри (4000–400 см-1) зняті на модулі ALPHA-Т спектрометра Bruker ALPHAFT-ІR. 1H ЯМР спектри сполук записані за допомогою спектрометра «Mercury 400» (розчинник – ДМСО-d6, внутрішній стандарт – тетраметилсилан). Хромато-мас-спектральні дослідження здійснили на приладі Agilent 1260 Series LC/MSD System. Висновки. Встановили оптимальні умови отримання ефірів 2-[5-((теофілін-7’-іл)метил)-4-R-1,2,4-тріазол-3-ілтіо]ацетатної кислоти. Синтезували 15 сполук, що не описані в науковій літературі раніше, структура яких підтверджена фізико-хімічними методами аналізу. Встановили, що синтез ефірів 2-[5-((теофілін-7’-іл)метил)-4-R-1,2,4-тріазол-3-ілтіо]ацетатної кислоти пе¬ребігає з більшим виходом, якщо їх отримувати безпосередньо з тіолу. Большие синтетические возможности и высокий биологический потенциал в ряду производных 1,2,4-триазола обусловливают благоприятные условия для поиска новых биологически активных веществ. Особую привлекательность также вызывает возмож¬ность введения различных заместителей на этапе формирования структуры 1,2,4-триазол-3-тиола. В то же время производные ксантина известны как основа для получения широкого спектра лекарственных средств. Цель работы – синтез и изучение свойств соединений в ряду сложных эфиров 2-[5-((теофиллин-7’-ил)метил)-4-R-1,2,4-три¬азол-3-илтио]ацетатной кислоты. Материалы и методы. Стратегия синтеза всех целевых продуктов реакции базировалась на использовании в качестве ис¬ходного вещества теофиллина. Для получения промежуточного тиола были использованы реакции этерификации, нуклеофильного замещения, гидразинолиза и внутримолекулярной щелочной гетероциклизации. Эфиры 2-[5-((теофиллин-7’-ил) метил)-4-R-1,2,4-триазол-3-илтио]ацетатных кислот получены двумя методами. Строение веществ подтверждено с помощью элементного анализа на приборе Elementar Vario ЕL cube (CHNS), ИК-спектры (4000–400 см-1) сняты на модуле ALPHA-Т спек¬трометра Bruker ALPHA FT-ІR. 1H ЯМР спектры соединений записаны с помощью спектрометра «Mercury 400» (растворитель – ДМСО-d6, внутренний стандарт – тетраметилсилан). Хромато-масс-спектральные исследования проводили на приборе Agilent 1260 Series LC/MSD System. Выводы. Установлены оптимальные условия получения эфиров 2-[5-((теофиллин-7’-ил)метил)-4-R-1,2,4-триазол-3-илтио] ацетатной кислоты. Синтезировано 15 ранее не описанных в научной литературе соединений, структура которых подтверждена физико-химическими методами анализа. Установлено, что синтез эфиров 2-[5-((теофиллин-7ʹ-ил)метил)-4-R-1,2,4-триазол-3- илтио]ацетатной кислоты протекает с большим выходом, если их получать непосредственно из тиола.
Синтез і властивості естерів 2-[4-R-5-(теофілін-7'-іл)-1,2,4-тріазол-3-ілтіо]ацетатної кислоти
Синтез и свойства эфиров 2-[5-((теофиллин-7’-ил)метил)-4-R-1,2,4-триазол-3-илтио]ацетатной кислоты
Keywords: 1,2,4-triazole; theophylline; physical properties; organic synthesis; esters; 1,2,4-тріазол; теофілін; фізичні властивості; органічний синтез; ефіри; 1,2,4-триазол; теофиллин; физико-химические свойства; органический синтез; эфиры